Helmholtz musicus: Die Objektivierung der Musik im 19. Jahrhundert durch Helmholtz Lehre von den Tonvorstellungen - Rieger, Matthias (Darmstadt Wissenschaftliche Buchgesellschaft, 2006)
The name of Hermann von Helmholtz?physiologist, physicist, polymath?has always been a staple of music-theoretical thought. But his position as a scientist, working at a time when musicology struggled to stand on its own feet and gain disciplinary independence, has typically accorded him an outsider's position in the history of music. Matthias Rieger argues in his provocative German dissertation, Helmholtz musicus, that musicologists ignore Helmholtz's impact on musical thought at their own peril.